2021
DOI: 10.31618/essa.2782-1994.2021.1.68.12
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Dust Pollution of Working Place Near Coal Dump

Abstract: The problem of estimating the level of air pollution in the working areas near the coal pile is considered. The task is to develop a CFD model that allows to predict the level of air dust pollution, taking into account the process of wetting the surface of the coal pile. To model the process of coal dust transfer in the air, a twodimensional mass transfer equation is used, which takes into account coal dust transfer due to convection and diffusion. The Navier-Stokes equations are used to calculate the air flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Berland [3]. This made it possible to calculate the value of the wind speed at an arbitrary height by the value of the speed of the incoming air flow at a control height above the earth's surface according to the power law [4][5][6][7]:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Berland [3]. This made it possible to calculate the value of the wind speed at an arbitrary height by the value of the speed of the incoming air flow at a control height above the earth's surface according to the power law [4][5][6][7]:…”
Section: Methodsmentioning
confidence: 99%
“…Mining companies play an important role in the country's export potential, as well as in the sustainable development of the regions where they are located [1][2][3][4][5]. However, each such enterprise is accompanied by waste storage facilities for mineral processing waste, which are mostly artificial formations on the earth's surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is this drift that forms the dust cloud near the tailings repository. To determine the speed of detachment of dust particles from the surface, experimental research methods are used [2]. This rate is related to the nature of the dust (e.g., dust from various tailings), dust moisture, dust particle size, material density, etc.…”
Section: Introductionmentioning
confidence: 99%
“…= ; dimensions of the calculation area 1800 m × 1000 m × 250 m. The emission rate of finely dispersed dust from the surface of the stack is calculated on the basis of empirical dependence[6]; it is assumed that the rate of gravitational settling of dust particles0.0001 s w = m/s. The predicted zone of dust pollution of the industrial site with a south-westerly wind direction is shown on the level 1.8 z = m (figure 2).…”
mentioning
confidence: 99%